The vindication of Daniel A. Carrion’s real portrait - Malpartida-Tello, Bertilo (2014)
After thorough research, a group of Medical Doctors discovered that, for the last 50 years, some members of the Peruvian Medical Professional College (PMPC) have been misleading the scientific community and the public opinions understanding of Daniel A. Carrions (DAC) historic figure. In effect, these members of the PMC have made public a fake portrait of the Peruvian Medical Doctor. In that way, DACs legacy has been distorted in several medical articles, in the press and in the media to the extent that false images were used in the process and replaced DACs real portrait with a fake image in all the PMPC offices nationwide. Since April of 2011, the researchers went through a thorough literature review, which included DACs book published in 1886, and several publications made by prominent Medical Doctors from the XIX, XX and XXI centuries. Those publications are reliable sources to understand DACs life, work and sacrifice. To fully understand DACs life, work and sacrifice, the researchers reviewed medical articles and press articles from the XIX century to the present. In that way, three books have been published to fully prove DACs real portrait. The document has several illustrations and photos that portrait DAC and his family. The evidence demonstrates which is DACs real portrait. Accordingly, the document will show the fallacies and mistakes made by the PMPC members who tried to impose DACs fake portrait. That information will be included in order to reflect these PMPC members effort to impose a false and deceptive portrait.